2023
DOI: 10.1007/s00167-023-07587-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased TT–TG distance caused by excessive tibiofemoral rotation predicts poor clinical outcomes after tibial tubercle osteotomy in recurrent patellar dislocation

Zhi‐jun Zhang,
Zheng Feng,
Menglinqian Di
et al.

Abstract: Purpose To compare clinical outcome between recurrent patellar dislocation (RPD) with or without actual tibial tubercle lateralisation (TTL) after medial patellofemoral ligament reconstruction (MPFL-R) combined with tibial tubercle transfer. Methods From 2015 to 2018, a total of 172 knees with RPD and a tibial tubercle-trochlear groove (TT-TG) distance of > 20 mm were treated with MPFL-R combined with tibial tubercle transfer. Patients were divided into the lateralisation group (TT-PCL > 24 mm, n = 74) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…A recent study also found that patients with unaddressed femoral torsion >30°, where MPFL and a TTO were performed, have lower clinical outcomes than patients with less torsion [ 36 ]. In light of these findings, it might be advisable to systematically assess torsion in addition to TT‐TG and correct at the morphologically most altered bone [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also found that patients with unaddressed femoral torsion >30°, where MPFL and a TTO were performed, have lower clinical outcomes than patients with less torsion [ 36 ]. In light of these findings, it might be advisable to systematically assess torsion in addition to TT‐TG and correct at the morphologically most altered bone [ 56 ].…”
Section: Discussionmentioning
confidence: 99%